Development of A Catheter-Associated Urinary Tract Infection (CAUTI) Prevention Supervision Instrument Based on The CDC Guideline for Prevention of CAUTI - Devi Rahma Sofia; Rizki Fitryasari; RR Dian Tristiana (Nursing Information Journal, 2026)
Catheter-Associated Urinary Tract Infection (CAUTI) remains one of the most common healthcare-associated infections and contributes significantly to increased morbidity, length of hospital stay, and healthcare costs. Suboptimal prevention practices and a lack of structured supervision instruments may lead to inconsistent adherence to evidence-based guidelines. This study aims to develop a supervision instrument for CAUTI prevention based on the CDC Guideline for Prevention of CAUTI. This study used a descriptive mixed-methods Research and Development (R&D) design, combining quantitative document analysis and qualitative interviews. A total of 100 patient monitoring documents were selected using purposive sampling, along with 7 ward head nurses as interview participants. Data were collected through document evaluation and semi-structured interviews, followed by Focus Group Discussion (FGD), expert consultation, and content validity testing using I-CVI. The developed instruments include a CAUTI prevention instrument for catheter insertion, as well as an instrument for prevention during catheter care and infection monitoring. The development encompassed the supervision format (including soft skills competency, interpretation), prevention content during catheter insertion, and prevention content during catheter care and infection monitoring. The validity test results for both instruments showed an I-CVI of 1.00, indicating that the instruments are valid and relevant. The developed instrument is expected to support the achievement of quality CAUTI prevention services in accordance with current guidelines, providing a comprehensive and high-quality instrument to enhance patient safety.